Microemulsion gel electrolyte, preparation method thereof and solid-state lithium battery

By using microemulsion interface regulation and in-situ polymerization technology, a three-dimensional network structure of microemulsion gel electrolyte was constructed, which solved the problem of interface contact deterioration caused by the reduction of electrolyte content in lithium batteries, and achieved high energy density and long-cycle stable lithium battery performance.

CN121507077APending Publication Date: 2026-02-10NANKAI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511806142.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-03
Publication Date
2026-02-10

AI Technical Summary

Technical Problem

In existing lithium batteries, traditional liquid electrolytes pose risks of leakage and flammability, while solid-state batteries have low ionic conductivity and poor electrode/electrolyte interface contact, resulting in limited energy density and cycle stability. How to reduce the amount of electrolyte used without sacrificing interface stability has become a challenge.

Method used

By employing a synergistic mechanism of microemulsion interface regulation and in-situ polymerization, a gradient cross-linked three-dimensional network is constructed through the directional migration and in-situ polymerization of microemulsion gel electrolyte on the electrode surface. This optimizes the electrode/electrolyte interface contact, reduces the amount of electrolyte used, and maintains efficient ion transport.

Benefits of technology

While significantly reducing the amount of electrolyte used, it improves the energy density and cycle stability of lithium batteries, enhances lithium-ion transport efficiency and safety performance, and is suitable for high-energy-density, long-cycle-stable lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121507077A_ABST
    Figure CN121507077A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium battery electrolytes, and discloses a microemulsion gel electrolyte, a preparation method thereof and a solid-state lithium battery, the microemulsion gel electrolyte is composed of a continuous phase (a solvent, a double lithium salt solute, a monomer and an initiator), an insoluble phase (a perfluorinated compound) and an amphiphilic phase (a fluorine-containing ether compound), the three phases form the microemulsion gel electrolyte with a three-dimensional network structure through microemulsion and thermal polymerization, the process is simple, and large-scale production is easy to realize. According to the electrolyte, fluorine-containing micelles are driven by liquid-liquid interfacial tension to spontaneously migrate to an electrode interface to form a LiF-rich protective layer, and meanwhile, monomers are initiated to directionally polymerize to construct a three-dimensional network structure. Through the synergistic effect, a stable interface under the ultralow electrolyte dosage (0.9 g / Ah) is achieved, the lithium-rich manganese-based positive electrode is matched to assemble a lithium-free negative electrode battery, the energy density reaches up to 698.20 Wh / kg, meanwhile, excellent safety performance is shown, and fire and smoke do not occur in an acupuncture test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery electrolyte technology, specifically to a microemulsion gel electrolyte and its preparation method, and a solid-state lithium battery. In particular, it relates to a microemulsion gel electrolyte with interface self-enrichment-three-dimensional network construction characteristics, its preparation method, and a solid-state lithium battery. Background Technology

[0002] In recent years, with the rapid development of electric vehicles, portable electronic devices, and large-scale energy storage systems, high-energy-density and high-safety lithium batteries have become a research hotspot. Traditional liquid lithium batteries, due to the use of large amounts of organic electrolytes, pose safety hazards such as leakage, volatilization, and flammability. While solid-state batteries offer high safety, their low ionic conductivity and poor electrode / electrolyte interface limit their practical applications. To improve the conductivity and safety of solid-state batteries, researchers have developed gel electrolytes. Gel electrolytes combine the high ionic conductivity of liquid electrolytes with the safety of solid-state electrolytes, but the electrolyte content still needs to be optimized to improve energy density. For example, Chinese patent CN117410575A, in order to maintain high ionic conductivity, still contains a large amount of liquid electrolyte components in its precursor solution, and the free solvent content in the system remains high after solidification. This means that it does not completely eliminate the risks of leakage and flammability inherent in liquid electrolytes, and the excessive electrolyte content also occupies internal battery space, limiting further improvements in energy density.

[0003] Therefore, reducing the amount of electrolyte is one of the key strategies for improving the energy density of lithium batteries. However, reducing the amount of electrolyte can lead to deterioration of the electrode / electrolyte interface contact, increase interfacial impedance, affect lithium-ion transport efficiency, and consequently reduce the rate performance and cycle stability of the battery. Therefore, how to reduce the amount of electrolyte without sacrificing interfacial stability has become a current research challenge. Summary of the Invention

[0004] To overcome the shortcomings of existing technologies, this invention provides a microemulsion gel electrolyte, its preparation method, and a solid-state lithium battery. By improving electrode / electrolyte interface compatibility through a synergistic mechanism of microemulsion interface regulation and in-situ polymerization, it maintains efficient ion transport while reducing electrolyte usage, thereby constructing a high-energy-density, long-cycle-stable lithium battery. This technology provides a new approach for the development of next-generation high-safety, high-energy-density energy storage devices. This microemulsion gel electrolyte requires a small amount of electrolyte while maintaining efficient ion transport.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: The first aspect of this invention provides a method for preparing a microemulsion gel electrolyte, comprising the following steps: (1) Preparation of continuous phase: Lithium salt, monomer and initiator are added to mixed carbonate solvent and stirred to obtain a homogeneous mixed solution A; (2) Introducing the amphiphilic phase: Add a fluorinated ether compound to the mixed solution A and stir at 500-600 rpm for 10-15 minutes to obtain mixed solution B; (3) Introducing an insoluble phase and microemulsifying: At a speed of 800±50 rpm, a perfluorinated compound was added dropwise to the mixed solution B for 20-30 minutes, followed by ultrasonic treatment to form a uniform nanomicelle dispersion; (4) In-situ thermal polymerization: The nanomicelle dispersion is heated to initiate an in-situ polymerization reaction to obtain microemulsion gel electrolyte.

[0006] Furthermore, the mixed carbonate solvent is a mixture of fluorocarbonate compounds and chain carbonate compounds in a volume ratio of 1:1 to 1:4.

[0007] More preferably, the fluorocarbonate compound is one or more of fluoroethylene carbonate, trifluoroethyl carbonate, and fluoromethyl ethyl carbonate; the chain carbonate compound is one or more of dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate.

[0008] Further, the lithium salt is one or more of lithium hexafluorophosphate, lithium difluorooxalate borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium tetrafluoroborate, and the molar concentration of the lithium salt in the mixed solution A is 1.0-1.4 mol / L, more preferably 1.2 mol / L.

[0009] Further, the monomer is one or more of N,N'-methylenebisacrylamide, pentaerythritol tetraacrylate, and fluoromethacrylate, and the mass fraction of the monomer in the mixed solution A is 0.5-4.0 wt%.

[0010] Furthermore, the initiator is azobisisobutyronitrile, and the mass fraction of the initiator in mixed solution A is 0.01-1 wt%.

[0011] Further, the fluorinated ether compound is selected from one or more of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, and trifluoroethoxyethylene fluorinated vinyl ether, and the volume fraction of the fluorinated ether compound in mixed solution B is 2.0-5.0 vol.

[0012] Further, the perfluorinated compound is one or more selected from 1,1,1,2,2,4,5,5,5-nonafluoro-4-(trifluoromethyl)-3-pentanone, perfluorohexanoyl fluoride, perfluorohexylsulfonyl fluoride, perfluoroalkyl ether, and perfluoropolyether, and the volume fraction of the perfluorinated compound in the nanomicelle dispersion is 1.0-4.0 vol.

[0013] Furthermore, the ultrasonic treatment frequency is 20-40 kHz, and the time is 5-10 minutes; the polymerization temperature is 50-70℃, and the time is 4-8 hours.

[0014] A second aspect of the present invention provides a microemulsion gel electrolyte prepared by the preparation method described above.

[0015] A third aspect of the present invention provides a solid-state lithium battery, including the microemulsion gel electrolyte.

[0016] Further, the preparation method of the solid-state lithium battery is as follows: high-voltage positive electrode material, binder, conductive agent and dispersant are stirred, and after being mixed evenly, solvent is added and stirring is continued until evenly mixed to form a positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector, dried and compacted to obtain a positive electrode sheet; the high-voltage positive electrode sheet and negative electrode sheet are assembled into a lithium battery cell by stacking or winding process, nano-micelle dispersion is injected into the cell, the battery is allowed to stand until the mixed solution fully wets the electrode, and the in-situ polymerization reaction is completed by heating to obtain a solid-state lithium battery.

[0017] Furthermore, the high-voltage positive electrode material is one or two of lithium-rich manganese-based materials and high-nickel ternary materials; the negative electrode sheet is one or two of copper foil and composite copper foil.

[0018] Furthermore, in the positive electrode slurry, the binder accounts for 2.0-3.5% by mass, the conductive agent accounts for 2.5-4.0% by mass, and the high-voltage positive electrode material accounts for 92-95% by mass; the areal loading of the double-sided positive electrode sheet is 56-62 mg / cm². 2 .

[0019] Furthermore, the binder is PVDF, and the conductive agent is one or both of conductive carbon black (super p) and carbon nanotubes (CNTs).

[0020] Furthermore, the settling time is 0.1h-1h.

[0021] Furthermore, the in-situ polymerization conditions are 50-70℃ and heating time of 4-8h.

[0022] The third aspect of this invention provides the application of the microemulsion gel electrolyte in the preparation of high-energy-density and high-safety solid-state lithium batteries.

[0023] This invention combines the unique interface regulation capabilities of microemulsion technology with in-situ gelation polymerization. Based on the synergistic mechanism of microemulsion interface regulation and in-situ polymerization, a microemulsion gel electrolyte with ultra-low interfacial tension, high permeability, and excellent interfacial wettability is developed. By introducing microemulsions into the gel electrolyte system, microemulsion micelles migrate directionally to the electrode surface under the drive of liquid-liquid interfacial tension, providing topological guidance for in-situ polymerization. This allows the polymer network to preferentially grow along the ion transport path, constructing a three-dimensional network with a gradient cross-linked structure. Simultaneously, the polymerization and solidification process locks in the optimized interfacial structure constructed by the micelles, preventing interfacial reconstruction during cycling. This optimizes the electrode / electrolyte interface contact, enhances lithium-ion transport efficiency, reduces electrolyte usage, increases battery energy density, stabilizes the lithium metal anode interface, inhibits dendrite growth, improves cycle life, and enhances safety performance.

[0024] Compared with the prior art, the present invention has the following advantages: (1) The preparation method can optimize the electrode / electrolyte interface by significantly reducing the amount of microemulsion gel electrolyte (0.9 g / Ah) through the synergistic effect of microemulsion interface regulation and in-situ gelation polymerization technology. It can achieve simultaneous improvement of battery energy density (>600 Wh / Kg) and cycle stability without relying on complex external field auxiliary equipment or excessive electrolyte injection.

[0025] (2) The microemulsion gel electrolyte of the present invention has a wide electrochemical window and can form a good match with ultra-high pressure lithium-rich manganese-based cathode materials, providing key technical support for the development of high safety and high energy density solid-state batteries.

[0026] (3) This preparation process simplifies the traditional preparation process and adopts operation steps that can be mass-produced. While maintaining excellent electrochemical performance, it has significant industrialization advantages and is particularly suitable for large-scale manufacturing applications in the field of power batteries. Attached Figure Description

[0027] Figure 1 An optical photograph of the microemulsion gel electrolyte prepared in Example 1 of this invention; Figure 2 This is a cross-sectional SEM image of the microemulsion gel electrolyte prepared in Example 1 of the present invention on an LRMO positive electrode sheet; Figure 3 Linear scanning voltammetry of the microemulsion gel electrolyte half-cell prepared in Example 1 of this invention; Figure 4 The ionic conductivity diagram is shown for the microemulsion gel electrolyte half-cell prepared in Example 1 of this invention. Figure 5The first-cycle discharge capacity-voltage curve of the lithium-rich manganese-based layered oxide / / composite copper foil battery prepared for Example 1 (microemulsion gel electrolyte) of the present invention; Figure 6 Comparison of the first-cycle discharge capacity-voltage curves of lithium-rich manganese-based layered oxide / / composite copper foil batteries prepared in Example 7 (microemulsion gel electrolyte) and Comparative Example 2 (gel electrolyte) of the present invention. Figure 7 Comparative graphs show the cycling tests of lithium-rich manganese-based layered oxide / composite copper foil batteries prepared in Example 7 (microemulsion gel electrolyte) and Comparative Example 2 (gel electrolyte) of the present invention. Figure 8 The first-cycle discharge capacity-voltage curve of the lithium-rich manganese-based layered oxide / composite copper foil battery prepared for Example 8 (microemulsion gel electrolyte) of the present invention. Detailed Implementation

[0028] The following are specific embodiments of the present invention. These embodiments are intended to further describe the present invention and are not intended to limit the present invention.

[0029] Example 1 A method for preparing a solid-state lithium battery based on a microemulsion gel electrolyte, comprising the following steps: (1) Preparation of continuous phase: Fluoroethylene carbonate and methyl ethyl carbonate were mixed uniformly at a volume ratio of 1:2. Then, 1.0 mol / L lithium hexafluorophosphate and 0.2 mol / L lithium difluorooxalate borate were added separately, and the mixture was stirred to form a homogeneous lithium salt solution. Finally, the monomer N,N'-methylenebisacrylamide and the initiator azobisisobutyronitrile were added, and the mixture was stirred until homogeneous to obtain mixed solution A. The mass ratio of lithium salt solution, monomer, and initiator was 96.8:3:0.2. (2) Introducing the parental phase: Add 2.0 vol% of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether to mixed solution A, and stir at 500 rpm for 15 minutes to obtain mixed solution B; (3) Introducing an insoluble phase and microemulsifying: At a rotation speed of 850 rpm, 1.0 vol% of 1,1,1,2,2,4,5,5,5-nonafluoro-4-(trifluoromethyl)-3-pentanone was added dropwise to mixed solution B. After 20 minutes, the mixture was sonicated for 5 minutes to form a uniform nanomicelle dispersion.

[0030] (4) In-situ thermal polymerization: 1) Lithium-rich manganese-based cathode material (LRMO), PVDF, super p and CNTs were stirred in a mass ratio of 95:2.5:2:0.5. After mixing evenly, NMP was added and stirring was continued until the cathode slurry was obtained. 2) The positive electrode slurry is uniformly coated on the surface of the positive electrode current collector (Al foil), dried, and compacted to obtain the positive electrode sheet. The double-sided areal loading of the positive electrode sheet is 57 mg / cm³. 2 ; 3) The positive electrode sheet and 6.5μm composite copper foil (purchased from Suzhou Luoming New Materials Co., Ltd.; item number: sputtered composite copper foil) were assembled into a 6.2Ah lithium-free negative electrode battery cell using a stacking process. Nano-micelle dispersion was injected into the cell, and the electrolyte dosage was 0.9 g / Ah. The battery was allowed to stand until the electrolyte fully wetted the electrodes. The in-situ polymerization reaction was then completed by heating at 60℃ for 5 hours to obtain a solid-state lithium battery.

[0031] Optical photographs of the microemulsion gel electrolyte prepared in Example 1 are shown below. Figure 1 As shown; cross-sectional SEM image of the microemulsion gel electrolyte on the LRMO cathode is shown below. Figure 2 As shown, the surface of the cathode material is covered with a microemulsion gel electrolyte layer with a thickness of approximately 2 μm. The interface between the microemulsion gel electrolyte layer and the surface of the active material exhibits a uniform and continuous characteristic.

[0032] Example 2 The difference from Example 1 is only in steps (2) and (3). 2.0 vol% of bis(2,2,2-trifluoroethyl) ether is added to mixed solution A and stirred at 500 rpm for 15 minutes to obtain mixed solution B. 1.0 vol% of perfluorohexanoyl fluoride is added dropwise to mixed solution B at 850 rpm for 20 minutes and then sonicated for 5 minutes to form a uniform nanomicelle dispersion.

[0033] Example 3 The only difference from Example 1 is step (3), in which 1.0 vol% of perfluorohexyl sulfonyl fluoride is added dropwise to the mixed solution B at a speed of 850 rpm for 20 minutes, followed by ultrasonic treatment for 5 minutes to form a uniform nanomicelle dispersion.

[0034] Example 4 The difference from Example 1 is only in steps (2) and (3). 2.0 vol% of trifluoroethoxyethylene fluorinated vinyl ether is added to mixed solution A and stirred at 500 rpm for 15 minutes to obtain mixed solution B. 1.0 vol% of perfluoropolyether is added dropwise to mixed solution B at 850 rpm for 20 minutes and then sonicated for 5 minutes to form a uniform nanomicelle dispersion.

[0035] Example 5 The only difference from Example 1 is step (3), in which 0.5 vol% of 1, 1, 1, 2, 2, 4, 5, 5, 5-nonafluoro-4-(trifluoromethyl)-3-pentanone is added dropwise to mixed solution B at a speed of 850 rpm for 20 minutes, followed by ultrasonic treatment for 5 minutes to form a uniform nanomicelle dispersion.

[0036] Example 6 The only difference from Example 1 is that in step (4), the amount of electrolyte used is 1.0 g / Ah.

[0037] Example 7 The only difference from Example 1 is that in step (4), the amount of electrolyte used is 1.5 g / Ah.

[0038] Example 8 The only difference from Example 1 is that in step (4), the amount of electrolyte used is 0.93 g / Ah, and a 17.4Ah lithium-free negative electrode battery cell is used.

[0039] Example 9 The only difference from Example 1 is that in step (4), a 17.4Ah lithium-free negative electrode battery cell is used. [xiaoyu1] Comparative Example 1 A method for preparing a solid-state lithium battery, comprising the following steps: (1) Preparation of gel electrolyte: Fluoroethylene carbonate and methyl ethyl carbonate were mixed uniformly at a volume ratio of 1:2. Then, 1.0 mol / L lithium hexafluorophosphate and 0.2 mol / L lithium difluorooxalate borate were added separately, and the mixture was stirred to form a lithium salt solution. Finally, the monomer N,N'-methylenebisacrylamide and the initiator azobisisobutyronitrile were added, and the mixture was stirred until homogeneous to obtain mixed solution A. The mass ratio of lithium salt solution, monomer, and initiator was 96.8:3:0.2. (2) In-situ thermal polymerization: The lithium-rich manganese-based cathode material (LRMO), PVDF, super p and CNTs were stirred in a mass ratio of 95:2.5:2:0.5. After mixing evenly, NMP was added and stirring was continued until the cathode slurry was obtained. The positive electrode slurry was uniformly coated onto the surface of an Al foil, dried, and compacted to obtain the positive electrode sheet. The double-sided areal loading of the positive electrode sheet was 57 mg / cm². 2 ; A 6.2Ah lithium-free negative electrode battery cell was assembled from a positive electrode sheet and a 6.5μm composite copper foil using a stacking process. Mixed solution A was injected into the cell, with an electrolyte content of 0.9g / Ah. The battery was allowed to stand until the electrolyte fully wetted the electrodes, and then an in-situ polymerization reaction was completed by heating at 60℃ for 5 hours to obtain a solid-state lithium battery.

[0040] Comparative Example 2 The only difference from Comparative Example 1 is that the positive electrode sheet and 6.5μm composite copper foil were assembled into a 9.5Ah lithium-free negative electrode battery cell using a stacking process. Mixed solution A was injected into the cell, and the electrolyte dosage was 1.5g / Ah. The battery was allowed to stand for a long time until the electrolyte fully wetted the electrodes, and then the in-situ polymerization reaction was completed by heating at 60℃ for 5 hours to obtain a solid-state lithium battery.

[0041] Comparative Example 3 A method for preparing a liquid lithium battery, comprising the following steps: Preparation of continuous phase: Fluoroethylene carbonate and methyl ethyl carbonate were mixed uniformly at a volume ratio of 1:2. Then, 1.0 mol / L lithium hexafluorophosphate and 0.2 mol / L lithium difluorooxalate borate were added separately and stirred to form a homogeneous solution. Introducing parental phase: Add 2.0 vol% of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether to the homogeneous solution and stir at 500 rpm for 15 minutes to obtain a mixed solution; Introducing an insoluble phase and microemulsifying: At a rotation speed of 850 rpm, 1.0 vol% of 1,1,1,2,2,4,5,5,5-nonafluoro-4-(trifluoromethyl)-3-pentanone was added dropwise to the mixed solution. After 20 minutes, the solution was sonicated for 5 minutes to form a uniform nanomicelle dispersion.

[0042] Lithium-rich manganese-based cathode material (LRMO), PVDF, super p, and CNTs were mixed at a mass ratio of 95:2.5:2:0.5. After thorough mixing, NMP was added and mixing continued until homogeneous, resulting in a cathode slurry. The cathode slurry was then uniformly coated onto an Al foil surface, dried, and compacted to obtain a cathode sheet. The double-sided areal loading of the cathode sheet was 57 mg / cm². 2 A 6.2Ah lithium-free negative electrode battery cell was assembled by stacking a positive electrode sheet with a 6.5μm composite copper foil. Nanomic micelle dispersions were injected into the cell, and the electrolyte concentration was 1.0 g / Ah. The battery was allowed to stand for a sufficient amount of time until the electrolyte fully wetted the electrodes, thus obtaining the lithium battery.

[0043] The materials and amounts of the battery cells used in the examples and comparative examples are shown in Table 1.

[0044] Table 1

[0045]

[0046] In Examples 1-4, different microemulsion reagents were used, but the ratio of amphiphilic to insoluble phases was the same. Examples 5 and 1 used the same microemulsion reagents, but the ratio of amphiphilic to insoluble phases differed. Examples 6, 7, and 1 used the same microemulsion reagents, but the amount of electrolyte added to the battery cell differed. Comparative Examples 1 and 2 used gel electrolytes, without either an amphiphilic or insoluble phase.

[0047] Performance testing A battery was assembled using a stainless steel sheet as the working electrode and lithium metal as the counter electrode. The electrochemical window of the microemulsion gel electrolyte prepared in Example 1 was tested using linear sweep voltammetry. Figure 3 The LSV curve of the microemulsion gel electrolyte prepared in Example 1 was measured at a scan rate of 1 mV / s. No obvious oxidative decomposition current was observed in the microemulsion gel electrolyte prepared in Example 1 between 2V and 6V, which fully demonstrates the high voltage resistance of the microemulsion gel electrolyte prepared in Example 1.

[0048] The battery was assembled using stainless steel sheets as the working and counter electrodes, and tested by electrochemical impedance spectroscopy (EIS) at 25 °C with a frequency range of 0.1 Hz to 1 MHz. Figure 4 The ionic conductivity of the microemulsion gel electrolyte prepared in Example 1 at 25°C is shown, with a room temperature conductivity of 1.6 mS / cm.

[0049] Further comparisons were made of the first-cycle energy density, cycle stability, and safety performance of full cells assembled with different gel electrolytes.

[0050] The solid-state lithium batteries prepared in Examples 1, 7, and 2 were placed at 25°C and charged at a constant current of 0.05C to the upper limit voltage of 4.8V, and then left to stand for 1 minute. They were then discharged at a constant current of 0.05C to the lower limit voltage of 2.0V. This constitutes one charge-discharge cycle, and the energy density is recorded as the energy density of the first cycle. This charging / discharging process was repeated until the ratio of the discharge capacity to the first discharge capacity in a certain cycle was ≤80%. The number of cycles experienced is the cycle life. Figure 5 First-cycle discharge capacity-voltage curve of the solid-state lithium battery prepared for Example 1 (microemulsion gel electrolyte); Figure 6 A comparison of the first-cycle discharge capacity-voltage curves of solid-state lithium batteries prepared in Example 7 (microemulsion gel electrolyte) and Comparative Example 2 (gel electrolyte); Figure 7This is a comparison graph showing the cycle test results of solid-state lithium batteries prepared in Example 7 (microemulsion gel electrolyte) and Comparative Example 2 (gel electrolyte). Figure 8 First-cycle discharge capacity-voltage curve of the lithium-rich manganese-based layered oxide / composite copper foil battery prepared for Example 8 (microemulsion gel electrolyte).

[0051] The solid-state lithium batteries prepared in the examples and comparative examples were placed in an environment of 25°C, charged at a constant current of 0.5C to 4.6V, and then charged at a constant voltage to a current ≤0.05C, and left to stand for 30 minutes. A high-temperature resistant steel needle with a diameter of Ф(5.0±0.2)mm was used to penetrate the geometric center of the battery from a direction perpendicular to the battery plates at a speed of (25mm±2.5mm / s) (the steel needle remained in the battery). The battery was observed for 60 minutes to see if it caught fire or exploded.

[0052] The test results are shown in Table 2.

[0053] Table 2 Test data for the examples and comparative examples

[0054] As shown in Table 1, the cells maintained normal operation when the amount of microemulsion gel electrolyte used in this invention ranged from 1.5 to 0.9 g / Ah. Under extremely low electrolyte usage (0.90–0.93 g / Ah), this technology achieved a significant increase in energy density: at 0.90 g / Ah (the minimum effective amount), the energy density of the 6.2 Ah cell reached 614.73 Wh / kg; at 0.93 g / Ah, the energy density of the 17.4 Ah cell further increased to 698.20 Wh / kg.

[0055] This invention, through the synergistic effect of microemulsion interface regulation and in-situ polymerization technology, offers significant advantages over microemulsion electrolytes and conventional gel electrolytes without added microemulsions: Compared to microemulsion electrolytes, the microemulsion gel electrolyte of this invention effectively enhances interfacial stability and strengthens dendrite suppression through its three-dimensional network structure, thereby improving cycle life; compared to conventional gel electrolytes, under extremely low dosage conditions of 0.9 g / Ah, conventional gel electrolytes fail to function properly due to insufficient electrolyte content leading to poor interfacial contact, hindered ion transport, and exacerbated interfacial side reactions. However, the microemulsion gel electrolyte of this invention, through its interfacial self-enrichment characteristics and in-situ construction of a LiF-rich interfacial layer, significantly improves the electrode / electrolyte interfacial contact, maintaining excellent electrochemical performance even at extremely low electrolyte dosages. This invention can reduce electrolyte dosage by 40% while maintaining the same energy density level. Specifically, when using a 6.2 Ah cell, the first-cycle energy density exceeds 600 Wh / Kg, reaching a maximum of 616.20 Wh / Kg. When using a 17.4Ah cell, under extremely low electrolyte usage (0.93 and 0.90 g / Ah), through staged formation process optimization, the cell energy density can reach 698.20 and 693.81 Wh / Kg, significantly higher than conventional designs. When the electrolyte usage is 1.5 g / Ah, the cell assembled with microemulsion gel electrolyte shows a 30% higher cycle capacity retention rate than the cell assembled with conventional gel electrolyte. This technology optimizes the electrode / electrolyte interface characteristics, ensuring battery safety while reducing electrolyte usage. Examples 1-5 and 8-9 all passed the nail penetration test with 100% success rate, without fire or explosion, demonstrating excellent safety performance. This invention provides an innovative solution for the development of high-energy-density, safe, and reliable lithium batteries.

[0056] Examples 6 and 7 investigated the effect of the amount of microemulsion gel electrolyte on battery performance. The results showed that as the amount increased from 0.9 g / Ah (Example 1) to 1.5 g / Ah (Example 7), the cycle life of the battery increased from 8 cycles to 13 cycles, demonstrating that the electrolyte system can maintain good electrochemical performance over a wide range of dosages.

[0057] The cell usage was the same in Comparative Example 3 and Example 6. Comparative Example 3 did not undergo in-situ polymerization, and its battery cycle life decreased by 11% compared to Example 6. The mechanical support provided by the gel matrix and the interface regulation function of the microemulsion produced a synergistic effect. The microemulsion gel electrolyte optimized the interface structure through in-situ polymerization and solidification. While retaining the intrinsic advantages of microemulsion, it improved the problem of dynamic instability of the interface in the liquid system and enhanced the cycle stability.

[0058] The above embodiments are merely preferred embodiments of the present invention, intended only to illustrate the technical concept and features of the present invention. Their purpose is to enable those skilled in the art to further understand the content of the present invention and implement it accordingly, and should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made according to the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a microemulsion gel electrolyte, characterized in that, Includes the following steps: (1) Preparation of continuous phase: Lithium salt, monomer and initiator are added to mixed carbonate solvent and stirred to obtain a homogeneous mixed solution A; (2) Introducing the amphiphilic phase: Add a fluorinated ether compound to the mixed solution A and stir at 500-600 rpm for 10-15 minutes to obtain mixed solution B; (3) Introducing an insoluble phase and microemulsifying: At a rotation speed of 800±50 rpm, a perfluorinated compound was added dropwise to the mixed solution B for 20-30 minutes, followed by ultrasonic treatment to form a uniform nanomicelle dispersion; (4) In-situ thermal polymerization: The nanomicelle dispersion is heated to initiate an in-situ polymerization reaction to obtain microemulsion gel electrolyte.

2. The preparation method according to claim 1, characterized in that, The mixed carbonate solvent is a mixture of fluorocarbonate compounds and chain carbonate compounds in a volume ratio of 1:1 to 1:

4. The fluorocarbonate compounds are one or more of fluoroethylene carbonate, ethyl trifluorocarbonate, and methyl ethyl fluorocarbonate; the chain carbonate compounds are one or more of dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate.

3. The preparation method according to claim 1, characterized in that, The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium difluorooxalate borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium tetrafluoroborate, and the molar concentration of the lithium salt in the mixed solution A is 1.0-1.4 mol / L.

4. The preparation method according to claim 1, characterized in that, The monomer is one or more of N,N'-methylenebisacrylamide, pentaerythritol tetraacrylate, and fluoromethacrylate, and the mass fraction of the monomer in mixed solution A is 0.5-4.0 wt%. The initiator is azobisisobutyronitrile, and the mass fraction of the initiator in mixed solution A is 0.01-1 wt%.

5. The preparation method according to claim 1, characterized in that, The fluorinated ether compound is selected from one or more of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, and trifluoroethoxyethylene fluorinated vinyl ether, and the volume fraction of the fluorinated ether compound in mixed solution B is 2.0-5.0 vol%; the perfluorinated compound is selected from one or more of 1,1,1,2,2,4,5,5,5-nonafluoro-4-(trifluoromethyl)-3-pentanone, perfluorohexanoyl fluoride, perfluorohexylsulfonyl fluoride, perfluoroalkyl ether, and perfluoropolyether, and the volume fraction of the perfluorinated compound in the nanomicelle dispersion is 1.0-4.0 vol%.

6. The preparation method according to claim 1, characterized in that, The conditions for the in-situ polymerization are 50-70℃ and heating time of 4-8h.

7. A microemulsion gel electrolyte prepared by the preparation method according to any one of claims 1-6.

8. A solid-state lithium battery, characterized in that, Includes the microemulsion gel electrolyte as described in claim 7.

9. The solid-state lithium battery according to claim 8, characterized in that, The method for preparing the solid-state lithium battery is as follows: The positive electrode material, binder, conductive agent and dispersant are stirred and mixed evenly to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector, dried and compacted to obtain a positive electrode sheet; The positive and negative electrode sheets are assembled into a lithium battery cell. The nano micelle dispersion is injected into the cell and allowed to stand until the mixed solution fully wets the electrode. The mixture is then heated to carry out an in-situ polymerization reaction to obtain a solid-state lithium battery. The positive electrode material is one or two of lithium-rich manganese-based materials and high-nickel ternary materials; the negative electrode sheet is one or two of copper foil and composite copper foil.

10. The application of the microemulsion gel electrolyte as described in claim 7 in the preparation of high-energy-density, safe solid-state lithium batteries.

Citation Information

Patent Citations

  • Preparation method and application of metal lithium battery gel electrolyte

    CN117410575A